2021
DOI: 10.1002/art.41726
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Synovial Tissue–Derived Characteristics in a Nomogram for the Prediction of Treatment Response in Treatment‐Naive Rheumatoid Arthritis Patients

Abstract: Objective This study applied a synovitis score obtained during routine care from ultrasound (US)–guided biopsies of synovial tissue (ST) in patients with rheumatoid arthritis (RA) and patients with other inflammatory and noninflammatory joint diseases to identify pretreatment synovial biomarkers associated with disease characteristics, and to integrate the findings into a multiparameter nomogram for use in baseline prediction of diagnosis and treatment response in treatment‐naive rheumatoid arthritis (RA) pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“… 31 Two other studies interrogated ST infiltrate in early naïve versus resistant established RA versus RA in remission. 32 33 In one study, the authors report that the Krenn Synovitis Score (KSS) was higher in patients with early active than established RA and both were higher compared with patients in remission. 32 In addition, established RA resistant to TNFi had higher KSS and higher prevalence of B cell–rich synovitis than early untreated RA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 31 Two other studies interrogated ST infiltrate in early naïve versus resistant established RA versus RA in remission. 32 33 In one study, the authors report that the Krenn Synovitis Score (KSS) was higher in patients with early active than established RA and both were higher compared with patients in remission. 32 In addition, established RA resistant to TNFi had higher KSS and higher prevalence of B cell–rich synovitis than early untreated RA.…”
Section: Resultsmentioning
confidence: 99%
“… 32 33 In one study, the authors report that the Krenn Synovitis Score (KSS) was higher in patients with early active than established RA and both were higher compared with patients in remission. 32 In addition, established RA resistant to TNFi had higher KSS and higher prevalence of B cell–rich synovitis than early untreated RA. 33 It is important to note that the definition of ‘early’ and ‘established’ RA was variable across studies and this might explain the contradictory results observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While conducting this work, we realised that the paucity of literature on clinical applications of tissue analysis did not allow the formulation of PtC dedicated to the clinical aspects. Indeed, although recent publications propose encouraging data for the use of SB for diagnosis, outcome prediction or disease management in clinical practice, the task force felt that these aspects should be included in the research agenda 2 4 42–44. One major limitation encountered in the development of these PtC was the scarcity of literature appraising the practical aspects of tissue retrieval, handling and analysis.…”
Section: Discussionmentioning
confidence: 99%
“…(26) Single Cell-RNA Sequencing of Synovial Tissue Methods for single-cell RNA sequencing (scRNAseq) of synovial tissue have already been described in detail (27). Briefly, synovial tissue biopsies were collected from naive to treatment RA patients (n=4) and from RA patients in sustained clinical and ultrasound remission (n=4) at the SYNGem Biopsy Unit of the Fondazione Policlinico Universitario A. Gemelli IRCCS using US-guided minimally invasive technique (28). High-quality total RNAs (RIN >8) were used to construct Illumina mRNA sequencing libraries.…”
Section: Patient Samples and Cell Culturesmentioning
confidence: 99%